ARTIFICIAL INTELLIGENCE AND CYBERSECURITY AS A KEY DRIVER OF BUSINESS OPERATIONS TRANSFORMATION IN THE CONDITIONS OF THE DIGITAL ECONOMY (Web of Technology: Multidimensional Research Journal, 2025)
The digital economy is growing rapidly, especially in developing countries. However, the meaning and size of the digital economy are limited and varied. The purpose of this paper is to review the current state of knowledge in order to develop a definition of the digital economy and an estimate of its size. The paper argues that there are three relevant areas. At the core of the digital economy is the “digital sector”: the IT/ICT sector that produces essential digital products and services. The true “digital economy” – defined as “the part of economic output that is derived entirely or predominantly from digital technologies and whose business models are based on digital goods or services” – consists of the digital sector and emerging digital and platform services.